The Role of Some Medicinal Plants in the Management of Peptic Ulcer - Al-Jawad, Faruk H.; Ismael, Ahmed H.; Nile, Anees K.; Sahib, Ahmed S. (AL-Kindy College Medical Journal, 2011)
Background: Plants used in folk medicine forthe treatment of peptic ulcer diseases is a verypromising approach to overcome the limitations ofclassical medicines.Aim: To explore the efficacy of medicinalplants, namely turmeric, garlic and marshmallow,in eradication of H. pylori.Methods: This prospective study was carried outon 225 of well-known dyspeptic patients who weredivided into four groups; a control group (receivedclassical medical therapy) and three other groupsthat received one of the three medicinal plants,plus the same therapy used in the control group.The follow up was done by using a questionnaireform, endoscopic examination, and determinationof serum levels of anti H.pylori antibodies &gastrin by using ELISA test. In addition, liverenzymes were monitored by using spectrophotometerto prove the safety of medicinal plants.Results: The rate of recurrence of peptic ulcerdisease was decreased in patients who received thecombined therapy when compared to the patientsin control group. Medicinal plants were effectivein decreasing the recurrence of H. pylori infectionwhen each one of them was used in combinationwith the medical therapy without causing harmfuleffects on the liver.Conclusion: Turmeric, garlic & marshmalloware effective in management of peptic ulcer withlow cost.